Design of citizenship education model development through digital media in strengthening students' character - Suhaida, Dada; Sapriya; Nordin, Zaimuariffudin Shukri; Moad; Rianto, Hadi; Rizal, Yenni (Jurnal Civics: Media Kajian Kewarganegaraan, 2025)
This study focuses on designing and developing the Citizenship Education model to strengthen students' character. A continuous effort is needed to create several learning models that strengthen students' positive character. Hence, they remain enthusiastic about completing the lecture on time and are not eroded by life's challenges. It used development research. The analysis results are obtained from several stages: the first stage is an analysis by identifying problems and carrying out task analysis, the second stage is a design by concluding learning objectives, the third stage is a development by creating patterns and utilizing digital media, the fourth stage is an implementation by applying learning pattern that has been designed, and the fifth stage is an evaluation by observing of whether the learning pattern made can be appropriate based on initial beliefs. Referring to the development of the ADDIE instructional model, the next stage is adapted to develop the Citizenship Education learning model called MPC (Modification of Project Citizen). This model is designed to be based on digital media and is produced by considering the implementation of Citizenship Education in strengthening student character.